PENGARUH MODEL BLENDED LEARNING TERHADAP MOTIVASI SERTA HASIL BELAJAR MAHASISWA UNIVERSITAS NEGERI MAKASSAR - Andika Isma; Aditya Alamsyah Syarif; Awaliah Fitri Nur Ananda; Radha Hasda Halfis; Muh Juharman; M Miftach Fakhri (Sakura Digital Nusantara, 2023)
Learning is a reciprocal process where students need feedback from the teacher and vice versa in order to obtain more effective learning outcomes, therefore success in learning will be achieved when students and lecturers have availability in the learning process. The learning model applied greatly affects student motivation and learning outcomes. The purpose of this study is to determine the motivation and learning outcomes of students who apply the Blended Learning model. The type of research used is quantitative research. This research involved students at Makassar State University. The authors collected data using questionnaires. Data analysis using descriptive analysis of the likert scale. The result of this study is a Blended Learning learning model that has a positive impact on the motivation and learning outcomes of students of Makassar State University.